Efforts to Improve Fine Motoric Skills of Early Childhood through Coffee Dregs at Tkit Ar-Rahmah, Bener Meriah Regency - Iqlima Fitria Ningsih (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine how efforts to improve the fine motoric abilities of early childhood through coffee grounds at Tkit Ar-Rahmah, Bener Meriah Regency. using the method of class action research (PTK) descriptive qualitative model. The subject of this research is class B children totaling 24 children, of which there are 15 girls and 14 boys at the age of 5-6 years. The results of the achievement of action in cycle 1 showed that the percentage of children's fine motor skills was 37.5% undeveloped (BB), children who began to develop (MB) 41.67%, and children developing as expected (BSH) 20.83%. Whereas in cycle II there was a very good increase, namely with a percentage of 16.67% of children who developed as expected (BSH) and 83.33% of children who developed very well (BSB). Thus it can be concluded that there is an increase in children's fine motor skills through coffee grounds collage media in TKIT Ar-Rahmah, Bener Meriah district.